Muscling selection in swine and its effect on carcass traits - J D Wheat; Donald H Kropf; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1972)
We are attempting to develop a well-muscled line of Durocs by selecting for minimum back fat and maximum loin eye area as estimated by the Anscan and to form a control line by randomly selecting from the same base population. The lines will be compared for performance and carcass traits, including incidence of pale soft exudative carcasses. Expected and realized heritability estimates for carcass traits will be calculated.; Swine Day, Manhattan, KS, November 2, 1972
Keywords: Swine day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 193; Swine; Muscling; Carcass traits; Loin eye area